Financial Analysis from An Accounting Point of View - Mihaela Ungureanu (CES Working Papers, 2013)
Despite the developments which tend to relax the relationship between financial analysis and accounting, property information provided by the latter irreplaceable render its use for diagnostic approaches financial foundation. An efficient information system can provide relevant indicators to users based on accurate and real information and financial analysis results are based on a diagnosis of return and risk. The aim of this article is to present primarily the origin and evolution of the relationship between financial analysis and accounting, and the fundamental role which accounting holds, through the information it produces, into analysts' work. The used research method is the bibliographic one, being studied timely books and articles of the domain. Literature does not provide concrete answers to this problem, resolutions being expected especially from practitioners.
Keywords: D82; G14; M41; N80; 330; stock analysis; financial diagnosis; information; performance; normalization Romania